"[A] story about a child is scarier than one about an adult roughly 80% of the time": Creepypasta, Children's media, and the child in media discourse. (May 2022) - Pattee, Amy
"Creepypasta, " short works of original horror fiction and frightening images created primarily by amateurs and shared in online communities of like-minded readers and writers, use the language of horror to encode and offer commentary on issues of contemporary concern. A close reading of an exemplary text, "Candle Cove, " demonstrates how this and other similarly themed creepypasta represent vernacular contributions to discussions of young people's interactions with mass media that reflect a popular interest in both securing and disrupting the figure of the child constructed in media discourse.